Adaptation of corporate model of ukrainian aircraft product life cycle to the international methodology of systems engineering - Svitlana Kryvova; Constantine Zvorykin; Serhii Trubachev (Mechanics and Advanced Technologies, 2023)
Problems. Under the present-day conditions, the preservation of competences of Ukrainian aircraft construction enterprises will be determined by the possibility of enterprises attracting to participation in international cooperation programs and projects. But this is possible only on the condition of prior harmonization of the product development methodology adopted in Ukrainian aircraft construction to that used in the international aircraft construction projects.